2023
DOI: 10.1136/bjo-2022-322808
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results of atropine 0.01% efficacy in the myopia control in a European population

Abstract: AimsTo evaluate the efficacy and safety of 0.01% atropine eye-drops in controlling myopia progression over 5 years.MethodsExperimental, analytical, prospective, randomised and longitudinal study, in 361 right eyes from 361 children randomised into the control group (177 eyes without treatment) and treatment group (184 eyes with 0.01% atropine eye-drops). Children assigned to the treatment group used 0.01% atropine once a day every night and the control group’s children did not use any treatment or placebo. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…On the other hand, a lower rate of progression over 2 years has been observed among the untreated participants of a Spanish series, with a mean SE progression of − 0.76 D and an AL increase of 0.37 mm, versus − 0.51 D and 0.20 mm, respectively, in the atropine 0.01% treated group 26 . Interestingly, in another recent publication with Spanish children, the 5-year progression in the no-treatment group was − 0.92 ± 0.56 D, with an AL increase of 0.49 ± 0.34 mm 27 . These findings highlight the necessity to compare studies not only with similar age and ethnicity but also with similar baseline characteristics: the proportion of mild myopic patients in these two series seem to be higher than ours: a mean SE of − 2.14 D (range − 0.50 to − 4.50 D) is far from our − 3.57 D (range from − 2 to – 6 D).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, a lower rate of progression over 2 years has been observed among the untreated participants of a Spanish series, with a mean SE progression of − 0.76 D and an AL increase of 0.37 mm, versus − 0.51 D and 0.20 mm, respectively, in the atropine 0.01% treated group 26 . Interestingly, in another recent publication with Spanish children, the 5-year progression in the no-treatment group was − 0.92 ± 0.56 D, with an AL increase of 0.49 ± 0.34 mm 27 . These findings highlight the necessity to compare studies not only with similar age and ethnicity but also with similar baseline characteristics: the proportion of mild myopic patients in these two series seem to be higher than ours: a mean SE of − 2.14 D (range − 0.50 to − 4.50 D) is far from our − 3.57 D (range from − 2 to – 6 D).…”
Section: Discussionmentioning
confidence: 87%
“…Nors mažos dozės atropinas yra plačiai naudojamas visame pasaulyje, su Europos populiacija atliktų tyrimų yra tik keli. M. Moriche-Carretero ir Perez-Flores patvirtino 0,01% atropino efektyvumą stabdant trumparegystės progresavimą ispanų populiacijoje [24][25][26]. Danijos populiacijoje 0,01% atropino lašų efektyvumas nepatvirtintas [27].…”
Section: Diskusijaunclassified
“…Nustatytas vidutinis SE ir ašies ilgio pokytis siekė − 0,44 ± 0,41 D ir 0,27 ± 0,20 mm. Vidutinis SE pokytis vienerių metų laikotarpyje nustatytas mažesnis pradėjus lašinti atropiną (prieš gydymą − 1,01 ± 0,38 D, su atropino lašais 0,01% − 0,44 ± 0,41 D) [25,26]. Danijoje atlikto tyrimo metu vertintas 0,01% atropino lašų efektyvumas.…”
unclassified
“…Similarly, in another recently published systematic review the estimated mean difference (MD) for myopia progression for atropine was found to be 0.29 D (95% CI 0.22-0.36; p = 0.03) [58]. In the present review, the most recent 16 out of initial 41 articles on RCTs were analyzed (Supplementary Table 3): a noticeable difference between these studies can be observed in terms of sample size [107][108][109], study length and design [110][111][112][113][114], the age of the children studied [106,109], location of trial [115][116][117], and the different atropine doses, which varied between 0.0025% and 1%, as well as the application frequency of drops [110,114,118,119], and lastly their aims [109,111,112,120]. Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [109,110,114,115,[118][119][120].…”
Section: Atropinementioning
confidence: 99%
“…Almost half of the selected studies were conducted in East Asia, in predominately Chinese ethnic children [109,110,114,115,[118][119][120]. Four studies were conducted in Europe [107,111,112,116], two in India [113,117], one in Iran [108], one in the USA [121], and one in Australia [106]. Upon comparing these studies, it may be inferred that varying ethnic groups exhibit dosedependent differences in the pharmacokinetics and the effect of atropine.…”
Section: Atropinementioning
confidence: 99%